Exclusion of one pedigree affected by adult onset primary open angle glaucoma from linkage to the juvenile glaucoma locus on chromosome 1q21-q31. Issue 12 (December 1996) - Avramopoulos, D; Kitsos, G; Economou-Petersen, E; Grigoriadou, M; Vassilopoulos, D; Papageorgiou, C; Psilas, K; Petersen, M B
Abstract : A locus for autosomal dominant juvenile onset primary open angle glaucoma (POAG) was recently assigned to chromosome region 1q21-q31. In the present study, a large Greek family with autosomal dominant adult onset POAG was investigated using microsatellite markers. Exclusion of linkage of the adult onset POAG gene to the region D1S194-D1S191 was obtained in this pedigree. Therefore, the data provide evidence that juvenile and adult onset POAG are genetically distinct disease entities.